Human Anti-Streptokinase Antibodies Induce Platelet Aggregation in an Fc Receptor (CD32) Dependent Manner - Lebrazi, Jamal; Helft, Gérard; Abdelouahed, Mustapha; Elalamy, Ismaïl; Mirshahi, Massoud; Samama, Michel Meyer; Lecompte, Thomas (Thrombosis and Haemostasis, 1995)
Exposure to streptokinase (SK) elicits anti-SK antibodies (Abs), which inhibit fibrinolysis and induce platelet aggregation. The mechanism of the latter is not fully understood, although it seems to involve platelet binding by a plasminogen streptokinase and anti-SK ternary complex. Anti-SK Abs were purified by affinity chromatography from serum of patients having received SK for acute myocardial infarction (AMI), and were shown to be of the IgG type. Their effects were studied with (i) human platelets in citrated plasma in the presence of SK or acetylated plasminogen-SK activator complex (APSAC), and (ii) in washed platelets, resuspended in Tyrode buffer after lowering the ionic strength, in the presence of APSAC (which provides both SK and plasminogen). An antibody concentration-response curve was obtained, showing a plateau in the presence of 0.1 mg/ml IgG. By increasing the concentration of APSAC, we obtained a unimodal response curve, the optimal concentration of APSAC being 0.05 U/ml. Aggregation was suppressed by chelating calcium with EDTA, blocking fibrinogen binding by the synthetic peptide Arg-Gly-Asp-Ser (RGDS), and raising intraplatelet cAMP with Iloprost (a prostacyclin analogue). Aggregation required the interaction of the anti-SK Ab Fc domain with the platelet Fc-gamma receptor type II, also known as CD32, since: (i) it was blocked by the monoclonal antibody IV-3 directed against CD32, (ii) it did not occur with F(ab)’2 fragments, which block the response to the intact IgG. The clinical relevance of these platelet-activating anti-SK antibodies remains to be determined. Two factors might influence clinical outcome: (i) the amount and type of pre-existing anti-SK Abs; (ii) the known interindividual variability of the platelet response to binding and activation by IgG involving the CD32 molecule.